2018
DOI: 10.1186/s13054-018-2242-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a transcriptome profile associated with improvement of organ function in septic shock patients after early supportive therapy

Abstract: BackgroundSeptic shock is the most severe complication of sepsis and this syndrome is associated with high mortality. Treatment of septic shock remains largely supportive of hemodynamics and tissue perfusion. Early changes in organ function assessed by the Sequential Organ Function Assessment (SOFA) score are highly predictive of the outcome. However, the individual patient’s response to supportive therapy is very heterogeneous, and the mechanisms underlying this variable response remain elusive. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Moreover, we also used CIBERSORT to estimate cellular types and found the relative abundance of monocyte in enrolled patients, and this finding was in line with the increasing data to show the crucial role of monocyte in the pathogenesis of sepsis (Supplemental Figure 1) (7,31). Notably, the transcriptome was similar on day-1 among immunocompromised and immunocompetent patients (Figure 1A), and the findings highlight the crucial need of using paired day-1 and day-8 samples to address the dynamic transcriptome in patients with septic with high heterogeneity as shown in this study and the previous study (6). Furthermore, we employed functional pathway analysis to demonstrate the essential role of T cell immunity-relevant pathways among immunocompromised patients with sepsis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, we also used CIBERSORT to estimate cellular types and found the relative abundance of monocyte in enrolled patients, and this finding was in line with the increasing data to show the crucial role of monocyte in the pathogenesis of sepsis (Supplemental Figure 1) (7,31). Notably, the transcriptome was similar on day-1 among immunocompromised and immunocompetent patients (Figure 1A), and the findings highlight the crucial need of using paired day-1 and day-8 samples to address the dynamic transcriptome in patients with septic with high heterogeneity as shown in this study and the previous study (6). Furthermore, we employed functional pathway analysis to demonstrate the essential role of T cell immunity-relevant pathways among immunocompromised patients with sepsis.…”
Section: Discussionsupporting
confidence: 90%
“…Immunoparalysis, characterised by not only immunologic but also by metabolic dysregulation after sepsis, has been increasingly recognised and attributed to be one of the key biological bases of prolonged impact on long-term mortality in patients with sepsis (4,5). Recent advances in sequencing technology, such as RNA-Sequencing (RNA-Seq), immune repertoire sequencing, and single-cell RNA-Seq (sc-RNA-Seq), allow for addressing immunological and metabolic features in patients with sepsis and coronavirus disease 2019 (COVID-19) infection (6)(7)(8). Several studies have used MicroArray and RNA-Seq to identify the transcriptomic signature, so-called subendotype, in patients with sepsis, and the currently identified sepsis-associated subendotypes included early improvement of organ dysfunction after sepsis and the responsiveness of steroids in patients with a septic shock (6,9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in patients with sepsis also reports the identification of a transcriptome profile associated with improvement of organ function after early supportive therapy. Unfortunately, however, the study could not yet distinguish a profile based on gene expression immediately upon ICU admission [31].…”
Section: Immunologic Staging Of Sepsismentioning
confidence: 94%
“…The characterisation of patients at the molecular level is a promising approach to identify pathophysiological mechanisms and specific targets for new therapeutic interventions in critically-ill patients with a particular condition [8]. For example, we have previously shown that changes in the metabolome (lipidome in particular) and transcriptome may play a relevant role in early recovery of organ dysfunction in patients with septic shock [9,10].…”
Section: Introductionmentioning
confidence: 99%